2(x-1)^2+x=1用因式分解法解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 17:10:56
2(x-1)^2+x=1用因式分解法解2(x-1)^2+x=1用因式分解法解2(x-1)^2+x=1用因式分解法解2(x-1)²+(x-1)=0(x-1)[2(x-1)+1]=0(x-1)(
2(x-1)^2+x=1用因式分解法解
2(x-1)^2+x=1用因式分解法解
2(x-1)^2+x=1用因式分解法解
2(x-1)²+(x-1)=0
(x-1)[2(x-1)+1]=0
(x-1)(2x-1)=0
x-1=0或2x-1=0
所以x1=1,x2=1/2
3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.
用因式分解法解方程(5x-1)^2=2注意是用因式分解法
用因式分解法解(2x+3)(x+1)=(x+1)(x+3)
用因式分解法解方程:4x(2x+1)=3(2x+1)
x(2x-1)=3(1-2x)用因式分解法怎么解
用因式分解法解方程:(2x-1)(3x-4)=2x-1
3x(x-1)=2(x-1)用因式分解法解列方程
3x(x-1)=2(x-1)用因式分解法解,
用因式分解法解方程 2x(5x-1)=3(5x-1)
x(x-1)=2(1-x)求用因式分解法解方程,
用因式分解法解.3x(x-1)=2(x-1),
解方程:2x(x-1)-(1-x)=0(用因式分解法)
用因式分解法解一元二次方程(x-1)(x+2)=3(x+2)
用因式分解法解方程:3x(x-1)+2x=2
用因式分解法解方程:(2x-1)(3x+4)=2x-1.
用因式分解法解方程 (2x-1)-x-4x-4=0
用因式分解法解方程3x(5x+1)=10x+2
(x-1)2=1-x 因式分解法